Clinical and Economic Outcomes of Intravenous Brivaracetam Compared With Levetiracetam for the Treatment of Seizures in United States Hospitals - Beaty, Silky; Rosenthal, Ning A.; Gayle, Julie; Dongre, Prashant; Ricchetti-Masterson, Kristen (Frontiers in Neurology, 2021)
BACKGROUND: Seizures are common among hospitalized patients. Levetiracetam (LEV), a synaptic vesicle protein 2A (SV2A) ligand, is a common intravenous (IV) antiseizure medication option in hospitals. Brivaracetam (BRV), a selective SV2A ligand for treatment of focal seizures in patients ≥16 years, has greater binding affinity, higher lipophilicity and faster brain entry than IV LEV. Differences in clinical outcomes and associated costs between IV BRV and IV LEV in treating hospitalized seizure patients remain unknown. OBJECTIVES: To compare the clinical outcomes, costs and healthcare resource utilization between seizure patients treated with IV BRV and those with IV LEV within hospital setting. DESIGN/METHODS: Retrospective cohort analysis was performed using chargemaster data from 210 U.S. hospitals in Premier Healthcare Database. Adult patients (age ≥18 years) treated intravenously with LEV or BRV (with or without BZD) and a seizure discharge diagnosis between July 1, 2016 - December 31, 2019 were included. The cohorts were propensity score-matched 4:1 on baseline characteristics. Outcomes included intubation rates, intensive care unit (ICU) admission, length of stay (LOS), all-cause and seizure-related readmission, total hospitalization cost and in-hospital mortality. Multivariate regression analysis was performed to determine association between treatment and main outcomes adjusting for unbalanced confounders. RESULTS: A total of 450 patients were analyzed (IV LEV, n=360 vs. IV BRV, n=90). Patients treated with IV BRV had lower crude prevalence of ICU admission (14.4% vs 24.2%, P=0.05), intubation (0% vs. 1.1%, P=0.59), 30-day all-cause readmission (1.1% vs. 6.4%, P=0.06) and seizure-related 30-day readmission (0% vs. 4.2%, P=0.05) and similar mean total hospitalization costs ($13,715 vs. $13,419, P=0.91) and in-hospital mortality (4.4% vs. 3.9%, P=0.77). The adjusted odds for ICU admission (Adjusted odds ratio [aOR]=0.60; 95% confidence interval [CI]: 0.31, 1.16; P=0.13), 30-day all-cause readmission (aOR=0.17; 95% CI: 0.02, 1.24; P=0.08), and in-hospital mortality (aOR=1.15; 95% CI: 0.37, 3.58, P=0.81) were statistically similar between comparison groups. CONCLUSIONS: Use of IV BRV may provide an alternative to IV LEV for management of seizures in hospital setting due to lower or comparable prevalence of ICU admission, intubation, and 30-day seizure-related readmission. Additional studies with greater statistical power are needed to confirm these findings.